Effective Strategies under Constructivist Approach of Learning to Reduce Fear and Phobia in Mathematics - Shahida, Naghma; Jamal, Sajid (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Mathematics is a very important school subject because of its utility in practical life. It is correlated with all the school subjects and is crucial in the career choice, however it is characterized with the fear and phobia among students. Constructivist approach is one of the most effective approach in which learners take self-initiative with positive attitude, are actively engaged in learning and provided opportunity to learn at their own pace. This approach provides flexibility and even welcome of wrong answer in creative perspective because it focuses more on process rather than product. What are the strategies under constructivist approach of learning to reduce fear and phobia in mathematics? What are the exact causes of fear and phobia in mathematics in the opinion of mathematics teachers? This study was conducted to know the answers of the above mentioned questions empirically. A self-constructed interview schedule was administered on a sample of 50 secondary schools mathematics teachers of Aligarh district. The Qualitative analysis of data revealed that emphasizing much on timely test, not valuing the mistakes of students, telling again and again that mathematics is a difficult subject and not realizing the utility of mathematics in practical life are some of the important causes of fear and phobia towards mathematics. Further, teachers opined that focusing on inductive approach, developing confidence in learners, self-construction of knowledge, fun with informative activities, inculcating problem solving ability and focusing on basic skills in mathematics are some of the strategies to reduce fear and phobia in mathematics.  Effective strategies under constructivist approach will have the perpetual impact on the attitude of students towards mathematics as it results to learn it at their own ability and interest, thus reducing the fear and phobia in mathematics. The findings of the study, hence, will have much implications for the teachers as well as policy makers